Incentives to invest in the human capital of temporary agency workers - Stephanie Schmidt; Kirsten Thommes (Zeitschrift für Personalforschung (ZfP), 2007)
Growing diffusion of temporary agency work, in conjunction with the growing importance of human capital management, leads to the question who invests in the human capital of temporary agency workers. Therefore, we investigate the parties' incentives to invest and review the small number of existing empirical works. We show that there are incentives for all parties to invest even in general human capital, using the human capital theory and the concept of psychological contracts. Clients' incentives to invest crucially depend on their motives for using temporary agency work. Additionally, we analyze the evolving externalities of the investments and draw some conclusions concerning the implications for the further training of temporary agency workers.
Keywords: 330; temporary agency work; incentives for investments; human capital; psychological contract; Leiharbeit; Humanvermögen; Weiterbildung; Betriebliche Investitionspolitik; Mitarbeiterbindung